Colon cancer metastasis mimicking intraductal papillary neoplasm of the extra-hepatic bile duct. (2015) - Yamao, Takanobu; Hayashi, Hiromitsu; Higashi, Takaaki; Takeyama, Hideyuki; Kaida, Takayoshi; Nitta, Hidetoshi; Hashimoto, Daisuke; Chikamoto, Akira; Beppu, Toru; Baba, Hideo
Graphical abstract: Highlights: A rare case of colon cancer metastasis mimicking IPNB at the extra-hepatic bile duct. Immunohistochemical staining of cytokeratin was useful to identify the primary site. There may be an incidental metastatic route via the bile stream from liver metastases. Abstract: Introduction: An accurate diagnosis of the primary cancer in cases with metastatic lesions is quite important because misdiagnosis may lead to the selection of incorrect adjuvant therapy and worse long-term outcomes after surgery. The metastatic sites associated with the dissemination of colon cancer are well known and normally predictable, which includes the lymphatic, haematogenous, or peritoneal regions, while other locations are quite rare. Presentation of case: In this report, we present a case of colon cancer with an unusual metastatic pattern mimicking an intraductal papillary neoplasm of the bile duct (IPNB) present in the extra-hepatic bile duct with a cytokeratin (CK)-7–negative and CK-20–positive profile (intestinal type). Discussion: In the case of this patient who had a history of colon cancer, immunohistochemical staining for the CKs was useful for distinguishing between primary IPNB and colon cancer metastases. We suspect that the metastatic pattern of this case of colon cancer that mimicked IPNB at the extra-hepatic bile duct developed incidentally via the bile stream. Conclusion: This is a rare case of colon cancer metastasis mimicking IPNB at the extra-hepatic bile duct. Our findings also suggest that there may be an incidental 4th metastatic route via the bile stream.